Robust fault detection filter design for interconnected systems subject to packet dropouts and structure changes. Issue 3 (1st February 2018) - Li, Jian; Wu, Chun‐Yu; Su, Qingyu
Abstract : The problem of robust fault detection (FD) filter design for interconnected systems, and the problems of both packet dropouts and disconnected interconnections in these subsystems are studied. By modelling instances of disconnected interconnections among subsystems and packet dropouts in the measurement channel into independent subsystems, this study proposes a switched scheme that combines mode‐dependent average dwell time with event‐driven switching. A filter in which the FD system is exponentially stable and achieves a weighted L 2 performance can be derived from the optimal method of convex linear matrix inequalities. An example is given to demonstrate the effectiveness of the proposed method.